Adolescent Behavior Overview About Vaccine HPV (Human Papilloma Virus) for Cervical Cancer Prevention in SMAN 5 Pekanbaru Year 2017 - Berliana Irianti (Science Midwifery, 2020)
The HPV vaccine is one method of prevention by providing vaccines that can stimulate the immune system to produce antibodies that can prevent Human Papilloma Virus to infect cells that can cause cervical cancer and several other types of cancer. This study aims to determine the behavior (knowledge, attitude and practice) young women about HPV vaccine (Human Papilloma Virus) for the prevention of cervical cancer in SMAN 5 Pekanbaru 2018. This study is a quantitative analytic design with cross sectional approach. Held on February 15, 2018 at SMAN 5 Pekanbaru using primary data. A sample of 82 respondents using accidental sampling technique. The research instrument used a questionnaire, univariate data processing is presented in the form of a frequency distribution table. The survey results revealed that the majority of adolescents knowledgeable lower as much as 53.7% (44 respondents) have a negative attitude as much as 65.9% (54 respondents), and not willing to make the HPV vaccine 80.5% (66 respondents). Through this research is expected to respondent can continue to add information from various sources that HPV vaccination in adolescents can be accomplished.